The Controlling Factors of the Natural Gas Hydrate Accumulation in the Songnan Low Uplift, Qiongdongnan Basin, China - Wei, Yang; Zenggui, Kuang; Jinfeng, Ren; Jinqiang, Liang; Hong, Lu; Zijie, Ning; Chenlu, Xu; Hongfei, Lai; Rui, Chen; Bin, Zhao; Jing, Chen; Xi, Zhang; et al. (Frontiers in Earth Science, 2022)
Hydrocarbon charging stages and natural gas hydrate accumulation models were established in the Songnan Low Uplift, Qiongdongnan Basin (QDNB), China. Detailed geochemical, paleotemperature, and paleopressure analysis, seismic interpretation, and hydrocarbon charging characterization were conducted to investigate the controlling factors of natural gas hydrate accumulation. The Yacheng and Lingshui Formations in the Lingshui Sag were identified as effective source rocks. The δ13C1 values of the gas hydrates vary from -35.97‰ to -59.50‰, following a direction from the sag center to the low uplift, indicating that δ13C1 values became relatively lighter during the gas migration. Seismic data evidence revealed that large-scale faults, laterally-distributed sandstones, and gas chimneys were comprehensive, however efficient hydrocarbon migration pathways. Systematic overpressure was developed in the Yacheng and Huangliu Formations, which offer sufficient hydrocarbon migration impetus. Hydrocarbon-bearing aqueous inclusions and their coexisting aqueous inclusions were observed in the Huangliu Formation in the Lingshui Sag, indicating four stages of hydrocarbon charging in the QDNB. Based on comprehensive analysis in this research, two gas hydrate accumulation models were proposed in the Songnan Low Uplift, QDNB as: (a) mixture of gas migrated by large-scale faults and thermogenic-biogenic mixed gas model, and (b) gas hydrates from laterally-distributed sandstones sealed by MTDs.